Total Phenolic, Flavonoid Content and Antioxidative, α-amylase Inhibitory Activity of Phellinus gilvus Fruiting Body Extracts - Hong, Duong Thi; Quang, Dang Ngoc (VNU Journal of Science: Natural Sciences and Technology, 2022)
Fractions yielded from Phellinus gilvus fruiting bodies by liquid-liquid partition of methanol extract contained various bioactive compounds such as phenolics, flavonoids and terpenes. Butanol, water and ethyl acetate fractions had large amount of phenolics, 158.12 - 247.31 mg of gallic acid equivalents (GAE)/g and low amount of flavonoids, 21.74 - 36.05 mg of quercetin equivalents (QE)/g. These values highly correlated with their antioxidative activity including 1,1-diphenyl-2-picrylhydrazyl (DPPH) scavenging potential with IC 50 values of 84.5 -108.44 μg/mL and reducing power. These fractions showed moderate α-amylase inhibitory activity with IC 50 values of 4.77, 10.69 and 3.9 mg/mL, respectively.  P. gilvus fractions exhibited negligible inhibitory activity on the growth of tested Gram-positive and Gram-negative bacterial strains at the concentration of 20 mg/mL. The results suggest the utility of butanol, water, and ethyl acetate fractions from fruiting bodies of P. gilvus collected in Vietnam for further characterization in order to apply for diabetes or anti-aging prevention.